RANCANG BANGUN ALAT VACUUM FORMING UNTUK PENGEMASAN PRODUK - Zamheri, A.; Seprianto, Dicky; Eka F, Yogi; Wilza, Romi; W, Soegeng; Shiddiq, M Hadzik; Pasa, Doni Ahmad; Ryan Bagaskara, Kgs. Muhammad (AUSTENIT, 2022)
The use of plastic is now very much in human life today. The nature of plastic is easy to form, light, strong, rust-resistant, as a good electrical insulator and of course has a high economic value, this is what makes the use of plastic more and more even replacing the use of metal, wood and glass. This study aims to design and manufacture a vacuum forming packaging device using PET with a pressure of 10 kPa. The method used is the thermo forming method. Vacuum forming is the simplest method. Parameters selected to indicate the quality of the plastic mold include the type of plastic, heating temperature and pressure. As the material to be tested is plastic type of polyethylene terephthalate (PET) measuring 55.5 cm x 61.5 cm with a thickness of 0.30 mm, The heating temperature is set at a constant temperature of 200.